2005
DOI: 10.1097/01.inf.0000148882.97399.79
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Adenovirus Genome During Acute Infection in Normal Children

Abstract: Viral load assessment in clinical samples determined by quantitative PCR can be useful in the diagnosis of adenovirus infection in immunocompetent, febrile children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Various assays have used WB, PBMCs, plasma, and serum (Echavarria et al, 2001;Flomenberg et al, 1997;Gu et al, 2003;Heim et al, 2003;Lankester et al, 2002) and ADV has been demonstrated in all of these compartments. Lymphocytes or PBMCs have been proposed as primary sites of viral latency (Horowitz, 2001) in asymptomatic patients, while others have provided anecdotal evidence that most virus is extracellular during active infection (Shike et al, 2005). The findings described in the present study are consistent with this notion, in that both WB and plasma demonstrated consistently higher viral loads than did PBMC.…”
Section: Discussionsupporting
confidence: 94%
“…Various assays have used WB, PBMCs, plasma, and serum (Echavarria et al, 2001;Flomenberg et al, 1997;Gu et al, 2003;Heim et al, 2003;Lankester et al, 2002) and ADV has been demonstrated in all of these compartments. Lymphocytes or PBMCs have been proposed as primary sites of viral latency (Horowitz, 2001) in asymptomatic patients, while others have provided anecdotal evidence that most virus is extracellular during active infection (Shike et al, 2005). The findings described in the present study are consistent with this notion, in that both WB and plasma demonstrated consistently higher viral loads than did PBMC.…”
Section: Discussionsupporting
confidence: 94%
“…A PCR-based test using broadly cross-hybridizing primers is highly sensitive and specific but remains a research tool [37]. Immunofluorescence-based tests suffer from poor sensitivity (~50%), although these tests are highly specific, and a positive test result for cells from the nasopharynx suggests current infection [38].…”
Section: Discussionmentioning
confidence: 99%
“…Several real-time adenovirus home-brew PCRs have been developed, initially for bone marrow transplant (BMT) patients and recently for other patient populations (20,29,46,73,98). A commercial real-time PCR assay (adenovirus r-gene PCR) was recently developed and validated for the generic detection of all adenovirus serotypes.…”
Section: Molecular Methodsmentioning
confidence: 99%